(untitled) (International Journal of Built Environment and Sustainability, 2022)
Covid-19 has caused a global crisis that has affected various aspects of life, including urban spatial arrangement, such as arrangement of street vendors activities in urban public spaces. As one of the activities supports that have developed due to primary urban activities, street vendors often occupy public spaces, as can be seen in Simpang Lima in Semarang, a central business and culinary tourism district where street vendors sell their good on pedestrian ways. Moreover, these vendors have been stabilized to accommodate their existence in sustainable manner. Hence, it is necessary to review the adaption of this arrangement to pandemics, bearing in mind the necessity of precautions against Covid-19 and physical distancing in accordance with the recommendations of the World Health Organization (WHO). This research applied quantitative methods and obtained data by collecting questionnaires and observations, showing that street vendors’ spatial arrangement within the food court concept in Simpang Lima had been adaptive to the Covid-19 pandemic reviewed from space arrangement, vending facilities, and health protocol applications. Among the precautions implemented for each vendor are the arrangement of space using modular spaces of size 3 by 3 meters, so that each has their own adaptive space, in accordance with physical distancing; maintaining spaces properly ventilated; applying a distance of more than one meter between any two tables in the consumer dining space; washing utensils in running water to maximize cleanliness; and ensuring the availability of public sinks with running water for customers and the public.